Faktor-Faktor Kredit Mikro Bersama Terhadap Pengambilan Keputusan Di PT. BPR BKK Kebumen (Perseroda) - Sotya Partiwi Ediwijoyo; Blandina Hendrawardani; Wakhid Yuliyanto; Laela Ma’rufah (Jurnal E-Bis, 2023)
Lack of information about credit results in delays in paying installments. This study aims to learn more about the influence of variable interest rates, term and collateral at PT BPR BKK Kebumen on joint microcredit decision making. The sampling procedure for this research was a questionnaire with 65 respondents. This type of study is descriptive with a quantitative approach method. The conclusion of the study results shows that credit decision making is significantly influenced by interest rate, term and collateral factors which are also confirmed by the F test results of 18,667. The interest rate variable has a positive influence on joint microcredit decision making, while the term and collateral variables do not have a positive influence on joint microcredit decision making. It was concluded that the relationship between business actors in making credit decisions was influenced by the interest rate given to business actors at PT BPR BKK Kebumen. The interest rate factor is an important and main factor, there are also other factors besides the interest rate in making credit decisions. Increasing interest rates will influence a person's interest in making credit decisions.